Stabilization and Balance Exercise Benefits in Amyotrophic Lateral Sclerosis: A Case Report - Amin Kordi Yoosefinejad; Fatemeh Jabari; Mahnaz Setooni (Shiraz University of Medical Sciences, 2014)
Background: ALS is the most devastating form of motor neuron disease, and the chance of survival is 3 to 5 years after the diagnosis is made. The pathogenesis of the disease is unknown. Several upper and lower motor neuron symptoms such as weakness, gait bradykinesia, and muscle atrophy have been reported. The core muscles are considered to be the center of the functional kinetic chain due to the links with upper and lower limbs. Methods: The patient in this case study was a 42 year-old woman suffering from ALSfor two years prior to the study. She had typical upper and lower motor symptoms, but her chief complaints were inability to walk, standing balance impairment, and a tendency to fall posteriorly. She performed core stabilization exercises, which were done three times per day. She was followed for three months. Results: Core stabilization exercises improved her quality of life, and she could walk independently after three months of exercise. In addition, her tendency toward falling posteriorly was completely alleviated. Conclusion: Core stabilization exercises were beneficial to the patient, and she was satisfied because her quality of life had improved.